Prognostic and clinicopathological significance of Cks1 in cancer: Evidence from a meta‐analysis. Issue 8 (3rd January 2019) - Zhang, Yi; Chen, Yuting; You, Fan; Li, Wang; Lang, Zhiquan; Zou, Zhenhong
Abstract: Background: Cyclin‐dependent kinase subunit 1 (Cks1), as a highly conserved regulatory protein, has pleiotropic roles in cell cycle progression. As research progresses, increasingly more statistics show that Cks1 may be involved in the occurrence, development, and prognosis of a variety of tumors but the conclusions remain controversial. In addition, there has been no meta‐analysis demonstrating the correlation between Cks1 and cancer. Therefore, this meta‐analysis was performed to determine the prognostic and clinicopathological significance of Cks1 in various cancers. Methods: Systematic computer literature retrieval was conducted on the Web of Science, Embase, PubMed, CNKI, and Wanfang databases. Stata SE12.0 software was used in the quantitative meta‐analysis. The hazard ratio (HR) and relative risk (RR) were pooled to assess the relationship between Cks1 expression and overall survival (OS), disease‐free survival (DFS), and clinicopathological parameters. Results: Nineteen studies were included, totaling 2, 224 participants. High expression of Cks1 was significantly correlated with worse OS (HR, 2.62; 95% confidence interval [CI], 2.18–3.14; p  < 0.001) and poorer DFS (HR, 2.73; 95% CI, 1.83–4.08; p  < 0.001). In addition, high expression of Cks1 was related to lymph node metastasis (RR, 1.59; 95% CI, 1.22–2.07; p  = 0.001) and advanced T stage (RR, 1.14; 95% CI, 1.04–1.25; p  = 0.005). Conclusions: High Cks1 expression predicted poorer prognosis and worse clinicopathological parameters in various cancers. Increased Cks1 could be a significant prognostic biomarker for poor survival in patients with various cancers. Abstract : High Cks1 expression predicted poorer prognosis and worse clinicopathological parameters in various cancers. Increased Cks1 could be a significant prognostic biomarker for poor survival in patients with various cancers.